Uncovering roles of proteins in the Fanconi Anemia DNA repair pathway - Xu, H (2024)
Genome maintenance is a vital biological process for humans. DNA interstrand crosslink (ICL) is a type of DNA damage that can fail DNA replication and transcription. The Fanconi Anemia pathway (the FA pathway) is the key process for repairing ICLs. UHRF1 acts as the sensor to recognize ICLs, which then recruits Fanconi Anemia (FA) proteins and FA-associated proteins, including FANCD2. The mono-ubiquitination of FANCD2 is essential for activating the downstream FA pathway. This ubiquitination process is regulated by the CK2/PP2A axis and the ATR-mediated phosphorylation of FANCD2. Besides, UHRF1 is also known to be the partner of DNMT1 for the protection of the epigenome. However, three questions about these known processes require further exploration.